Wear-resistant and tensile composite material for rubber gloves and preparation method of wear-resistant and tensile composite material

Through the composite materials of modified rubber and modified polyborosilicon rubber, and the cross-linking network with high mechanical properties and flame retardant properties is formed by using processes such as refining and electronic radiation, the problems of insufficient wear resistance and flame retardant properties of existing composite materials for rubber gloves are solved, and the significant improvement of the material's performance is achieved.

CN119529459APending Publication Date: 2025-02-28DONGGUAN MINGKAI PLASTICS TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411859953.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The wear resistance and flame retardant properties of existing composite materials for rubber gloves need to be further improved.

Method used

A composite material of modified rubber and modified polyborosilicate rubber is used to form a crosslinking network with high mechanical properties and flame retardant properties through processes such as refining and electronic radiation.

Benefits of technology

It significantly improves the mechanical properties and flame retardant properties of the material, enhances the wear resistance and ability to extend life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192960260000031
    Figure BDA0005192960260000031
  • Figure BDA0005192960260000141
    Figure BDA0005192960260000141
  • Figure BDA0005192960260000151
    Figure BDA0005192960260000151
Patent Text Reader

Abstract

The invention discloses a wear-resistant tensile composite material for rubber gloves and a preparation method thereof, and belongs to the technical field of new materials, the wear-resistant tensile composite material comprises the following raw materials by weight: 80-100 parts of modified rubber, 10-15 parts of a filler, 3-5 parts of a plasticizer, 1-2 parts of an antioxidant, 2-3 parts of a heat stabilizer, 2-3 parts of a lubricant and 5-8 parts of a vulcanizing agent; the prepared expanded particles serve as polymerization base points of modified polyborosilicate rubber, promote fracture of disulfide bonds in modified ternary rubber and serve as radiation absorption centers to promote crosslinking of the expanded particles and the modified ternary rubber, the mechanical performance of the material is improved, a glassy protective layer is generated by a silicon-boron structure of the expanded particles in the combustion process and covers the surface of the material, and the service life of the material is prolonged. And carbonization of organic matters is promoted, so that the material forms a heat-insulating carbon layer, and the flame retardant property of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a wear-resistant and stretch-resistant composite material for rubber gloves and a preparation method thereof. Background Art

[0002] The wear-resistant and stretch-resistant composite material technology of rubber gloves is a combination of material science and industrial application. Traditional rubber gloves are difficult to cope with high-intensity stretching, friction and special environments. Adding composite materials such as nano-carbon fibers and polyamide fibers to rubber not only significantly improves its wear resistance and tensile strength, but also gives it flame retardant properties. The application of flame retardants or surface coatings allows the gloves to remain safe and intact even at high temperatures. This technology is widely used in industry, construction and medical fields to extend the life of gloves, reduce resource waste, and provide support for environmental protection and economic benefits. Wear-resistant and stretch-resistant materials give rubber gloves more functionality and also reflect the innovative value of modern material technology.

[0003] Prior art, CN103549689A discloses a wear-resistant rubber glove and a processing method thereof, wherein the wear-resistant rubber latex is composed of the following materials: 90-100 parts of nitrile rubber latex, 0.5-1.5 parts of sulfur, 0.5-1.5 parts of zinc oxide, 0.5-3.0 parts of titanium dioxide, 10-40 parts of carbon black and 0.5-1.5 parts of paraffin. The improved formula and process are used to effectively improve the wear resistance of the gloves and greatly increase the use efficacy of the rubber gloves.

[0004] However, the above patent content is to significantly enhance the wear resistance of the material by mixing nitrile rubber latex and auxiliary materials. However, since the inorganic components in the auxiliary materials are too high and the polarity difference between the inorganic components and nitrile rubber latex is large, the compatibility of the materials is reduced, resulting in weak interfacial bonding between the materials, resulting in the wear resistance of the material to be further improved, and a large amount of combustible auxiliary materials are filled inside the material, so the flame retardant performance of the material needs to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a wear-resistant and stretch-resistant composite material for rubber gloves and a preparation method thereof, so as to solve the technical problem that the wear resistance and flame retardancy of the composite material for rubber gloves in the prior art need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: A wear-resistant and stretch-resistant composite material for rubber gloves, comprising the following raw material components in parts by weight: 80-100 parts of modified rubber, 10-15 parts of filler, 3-5 parts of plasticizer, 1-2 parts of antioxidant, 2-3 parts of heat stabilizer, 2-3 parts of lubricant and 5-8 parts of vulcanizing agent;

[0008] The preparation method of the modified rubber comprises the following steps:

[0009] A1. Add the modified ternary rubber and modified polysilicon boron rubber into an internal mixer at a temperature of 200-210°C, mix for 12-15 minutes, and discharge the materials to obtain a modified rubber body;

[0010] A2. Placing the modified rubber body in an electron beam irradiation device to obtain the modified rubber after electron irradiation.

[0011] The reaction principle for preparing the modified rubber is as follows: under the high-temperature catalysis of the internal mixer, the zinc oxide inside the modified polysilicon boron rubber reduces the bond energy of the disulfide bond through electronic interaction with the disulfide bond, and the zinc oxide has Lewis base characteristics and can combine with the sulfur free radicals or vulcanization intermediates generated during the vulcanization process to form unstable sulfur oxides. The disulfide bonds will break to generate sulfur free radicals or monosulfide bonds, so that the material will be vulcanized to obtain a modified rubber blank; in the process of electron radiation, the boronized particles inside the modified polysilicon boron rubber act as radiation absorption centers, generate a large amount of heat, promote the breakage of a large number of double bonds on the modified polysilicon boron rubber and the internal chain segments of the modified ternary rubber to produce free radicals, and finally obtain the modified rubber through free radical reaction.

[0012] Furthermore, in step A1, the usage ratio of modified ternary rubber and modified polysilicon boron rubber is 2-3g:1g; in step A2, the operation of electron radiation is: nitrogen protection is introduced into the electron beam irradiation equipment at a flow rate of 10-15L / min, and the electron beam energy is set to 2-4MeV, the power is 18-20kW, the radiation dose is 180-240kGy, and the conveyor belt speed is set to 1-3m / min.

[0013] Furthermore, the preparation method of the modified ternary rubber is: allyl methyl disulfide, 2-methylacrylamide, 4-allyl-1,2-dimethoxybenzene, azobisisobutyronitrile and dimethyl sulfoxide are added to a reactor, the temperature of the reactor is increased to 60-80°C, and the reaction is kept warm for 2-3 hours, and then the modified liquid is added to the reactor, and the reaction is kept warm for 10-15 minutes, and the modified ternary rubber is obtained by post-treatment.

[0014] The formula for preparing modified ternary rubber is:

[0015]

[0016] Where: Wherein “*” represents the active site of the organic chain segment.

[0017] The reaction principle for preparing modified ternary rubber is as follows: under the catalysis of a free radical initiator, double bonds in allyl methyl disulfide, 2-methylacrylamide, and 4-allyl-1,2-dimethoxybenzene are broken to generate free radicals, and a long chain structure is obtained through continuous polymerization. The isocyanate group on the 3-isocyanatepropyltrimethoxysilane in the modified liquid reacts with the amino group inside the chain segment to finally prepare the modified ternary rubber.

[0018] Furthermore, the dosage ratio of allyl methyl disulfide, 2-methylacrylamide, 4-allyl-1,2-dimethoxybenzene, azobisisobutyronitrile, dimethyl sulfoxide and modifying liquid is 5-6g:3-4g:5-6g:1.2-1.6g:40-50mL:10-12mL, and the modifying liquid is composed of 3-isocyanatepropyltrimethoxysilane, triethylamine and dimethyl sulfoxide in a dosage ratio of 2-3g:0.2-0.3g:10-12mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is transferred to a rotary evaporator at a temperature of 80-90°C, and the solvent is evaporated under reduced pressure to obtain a modified ternary rubber.

[0019] Furthermore, the preparation method of the modified polysilicon boron rubber comprises the following steps:

[0020] B1. Add the modified microparticles, 5-chloro-2-methoxyphenylboronic acid, saturated sodium hydroxide solution and anhydrous ethanol to a three-necked flask in sequence, heat to 50-60° C. under magnetic stirring, and keep the constant temperature for 20-30 minutes. After the reaction is completed, perform post-treatment to obtain boronized microparticles;

[0021] The reaction principle for preparing boronized microparticles is as follows: the chlorine groups on 5-chloro-2-methoxyphenylboronic acid and the hydroxyl groups on the surface of the modified microparticles undergo elimination reactions to form a cross-linked structure, and finally a boron component is introduced into the modified microparticles to obtain expanded microparticles.

[0022] B2. Add boronated particles, 3-(methacryloyloxy)propyltrimethoxysilane, diphenyldimethoxysilane, triethylamine and N,N-dimethylformamide into a three-necked flask in sequence, raise the temperature to 60-80°C by oil bath heating, and stir the reaction at this temperature for 1-2 hours, then continue to add the end-capping agent to the system and react for 10-20 minutes. After the reaction is completed, perform post-treatment steps to obtain modified polysilicon boron rubber.

[0023] The reaction principle for preparing modified polysilicon boron rubber is as follows: under the catalysis of alkalinity and high temperature, the siloxy groups and boron hydroxyl groups are hydrolyzed to form a cross-linked structure with the boronized particles as the base point, and finally the modified polysilicon boron rubber is prepared.

[0024] Further, in step B1, the magnetic stirring rate is 80-120rpm, the amount ratio of modified zinc oxide particles, 5-chloro-2-methoxyphenylboronic acid, saturated sodium hydroxide solution and anhydrous ethanol is 5-8g:2-3g:0.5-0.8mL:30-40mL, and the post-treatment includes: after the temperature of the three-necked flask is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with anhydrous ethanol and deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried to constant weight to obtain boronized particles; in step B2, the boron The dosage ratio of the microparticles, 3-(methacryloyloxy)propyltrimethoxysilane, diphenyldimethoxysilane, triethylamine, N,N-dimethylformamide and the end-capping group is 8-10g:3-5g:4-6g:0.5-0.8g:50-60mL:1-2g, the end-capping agent is 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, and the post-treatment includes: when the temperature of the three-necked flask is lowered to room temperature, the reaction solution is transferred to a rotary evaporator with a temperature of 80-90°C, and the solvent is evaporated under reduced pressure to obtain a modified polysilicon boron rubber.

[0025] Furthermore, the preparation method of the modified microparticles comprises the following steps:

[0026] C1. Add tetraethyl orthosilicate, zinc nitrate and deionized water into a reaction kettle, stir at room temperature for 5-10 minutes, adjust the pH of the reaction system to 8-10 with a saturated sodium hydroxide solution, let stand for 8-12 hours to obtain an aged gel, and perform post-treatment to obtain a mixed gel;

[0027] C2. Transfer the mixed gel to a tubular furnace and calcine to obtain modified particles.

[0028] The reaction principle for preparing the modified microparticles is as follows: under alkaline conditions, the gel network structure formed by the hydrolysis of ethyl orthosilicate is mixed with the crystals produced by the hydrolysis of zinc nitrate, and after high-temperature calcination, the modified microparticles composed of silicon dioxide and zinc oxide are formed.

[0029] Furthermore, in step C1, the dosage ratio of tetraethyl orthosilicate, zinc nitrate and deionized water is 2-3g:4-6g:20-30mL, and the post-treatment includes: transferring the aged gel to a drying oven at a temperature of 80°C and vacuum drying to constant weight to obtain a mixed gel; in step C2, the calcination operation includes: after nitrogen protection is introduced into the tubular furnace, the tubular furnace is heated to 500-600°C at a heating rate of 3-5°C / min, and the heat treatment is carried out for 2-4h to obtain modified particles.

[0030] A method for preparing a wear-resistant and stretch-resistant composite material for rubber gloves comprises the following steps: adding modified rubber, modified particles, a plasticizer, an antioxidant, a heat stabilizer, a lubricant and a vulcanizer into a twin-screw extruder, melting and extruding the mixture into a molding die, and naturally cooling and shaping the mixture to obtain the composite material.

[0031] Furthermore, the temperatures of the six temperature zones of the twin-screw extruder from the feed end to the discharge end are 200°C, 205°C, 210°C, 210°C, 210°C, and 215°C, respectively, and the main shaft speed of the twin-screw extruder is 40-60rpm.

[0032] Furthermore, the filler is one or more of nano-silica particles, calcium carbonate and carbon black; the plasticizer is one or more of dibutyl phthalate, dioctyl phthalate and dioctyl terephthalate; the antioxidant is one or more of N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 2,6-di-tert-butylhydroquinone; the heat stabilizer is one or more of lead stearate, tribasic lead sulfate and epoxy soybean oil; the lubricant is one or more of stearic acid, polyethylene wax and paraffin; the vulcanizer is one or more of sulfur, thiuram disulfide and thiophenol dicarboxaldehyde.

[0033] The present invention has the following beneficial effects:

[0034] 1. The present invention prepares expanded particles, which serve as polymerization bases of modified polysilicon boron rubber, promote the breaking of disulfide bonds inside the modified ternary rubber to form active sites, promote the vulcanization and crosslinking of the modified ternary rubber and the modified polysilicon boron rubber, and at the same time, as a radiation absorption center, further promote the crosslinking of the two, significantly improving the mechanical properties of the material, and its silicon-boron structure generates a glassy protective layer covering the surface of the material during the combustion process, and the boron-oxygen structure promotes the carbonization of organic matter, so that the material forms an insulating carbon layer, significantly improving the flame retardant properties of the material.

[0035] 2. In the process of preparing the modified ternary rubber, the present invention introduces disulfide bonds and amino groups inside the modified ternary rubber. The disulfide bonds interact electronically with the zinc oxide component inside the modified polysilicon boron rubber during the mixing and kneading of the modified ternary rubber and the modified polysilicon boron rubber, thereby degrading the bond energy thereof. Due to the Lewis base characteristics of zinc oxide, the sulfur free radicals or vulcanization intermediates generated during the rupture of the disulfide bonds combine to form unstable sulfur oxides, and the disulfide bonds break to generate sulfur free radicals or monosulfide bonds, thereby vulcanizing the material and significantly improving the mechanical properties of the material. The amino groups inside the modified ternary rubber are modified by 3-isocyanate propyltrimethoxysilane, and silicon-oxygen bonds are introduced into the structure, thereby significantly improving the binding ability of the material with inorganic auxiliary materials and further improving the mechanical properties of the material.

[0036] 3. In the process of preparing the modified polysilicon boron rubber of the present invention, firstly, expanded particles are prepared, which serve as the polymerization center of the modified polysilicon boron rubber. During the combustion of the material, the boron oxygen chain segments will generate a glassy protective layer covering the surface of the material, isolating oxygen, reducing the contact between the combustible and the heat source, thereby inhibiting the continuation of the combustion reaction. In addition, the glassy protective layer has a high heat capacity, can absorb part of the heat during combustion, reduce the surface temperature of the material, delay the combustion process, and burn with the silicon oxygen chain segments to produce silicon dioxide, further forming an inorganic glassy protective film to prevent the combustion from spreading. In addition, the boron element can also catalyze the formation of a carbonized layer on the surface of the material, thereby playing an insulating role. The heat and oxygen isolation effects further inhibit the spread of flames; and the introduction of boron elements enables the modified polysilicon boron rubber to form a cross-linked network composed of boron oxygen bonds and silicon oxygen bonds. Boron oxygen bonds can provide additional chemical cross-linking points, greatly improving the cross-linking density of the material, thereby reducing the slippage and breakage of the molecular chain, so that the material can withstand higher stress when subjected to force, and the cross-linking structure is tighter, and the tensile strength and elongation of the material are also improved accordingly; and, compared with silicon oxygen bonds, boron oxygen bonds have higher rigidity and stronger tensile properties, and enhance the interaction between molecular chains, so that the material is not easily deformed under the action of external force, and can absorb and disperse more mechanical energy when subjected to force. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment provides a method for preparing a wear-resistant and stretch-resistant composite material for rubber gloves, comprising the following steps:

[0040] Step 1: Preparation of modified particles

[0041] Weigh: 240.0 g of tetraethyl orthosilicate, 420.0 g of zinc nitrate and 2.1 L of deionized water into a reactor, stir at room temperature for 5 min, adjust the pH of the reaction system to 8 using a saturated sodium hydroxide solution, and let it stand for 8 h to obtain an aged gel. Transfer the aged gel to a drying oven at 80° C. and vacuum dry to constant weight to obtain a mixed gel.

[0042] The mixed gel was transferred to a tubular furnace. After nitrogen protection was introduced into the tubular furnace, the temperature was increased to 500° C. at a heating rate of 3° C. / min and kept at this temperature for 2 h to obtain modified particles.

[0043] Step 2: Preparation of modified polysilicon boron rubber

[0044] Weigh: 540.0g modified microparticles, 240.0g 5-chloro-2-methoxyphenylboronic acid, 54.0mL saturated sodium hydroxide solution and 3.2L anhydrous ethanol are added to a three-necked flask in sequence, and the temperature is raised to 50°C under magnetic stirring conditions, the stirring rate is 80rpm, and the constant temperature reaction is maintained for 20min. After the reaction is completed, wait for the temperature of the three-necked flask to drop to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with anhydrous ethanol and deionized water for 3 times, and place the filter cake in a drying oven at a temperature of 80°C and vacuum dry to constant weight to obtain boronized microparticles;

[0045] Weigh: 810.0g of boronized microparticles, 360.0g of 3-(methacryloyloxy)propyltrimethoxysilane, 420.0g of diphenyldimethoxysilane, 54.0g of triethylamine and 5.4LN,N-dimethylformamide, add them into a three-necked flask in sequence, raise the temperature to 60°C by oil bath heating, and stir the reaction at this temperature for 1h, then continue to add 120.0g of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane to the system, react for 10min, after the reaction is completed, wait for the temperature of the three-necked flask to drop to room temperature, transfer the reaction solution to a rotary evaporator at a temperature of 80°C, and evaporate the solvent under reduced pressure to obtain modified polysilicon boron rubber.

[0046] Step 3: Modified ternary rubber

[0047] Weigh: 210.0 g of 3-isocyanatepropyltrimethoxysilane, 24.0 g of triethylamine and 1.0 L of dimethyl sulfoxide according to the amount ratio to prepare a modified solution;

[0048] Weigh: 540.0g allyl methyl disulfide, 360.0g 2-methacrylamide, 500.0g 4-allyl-1,2-dimethoxybenzene, 120.0g azobisisobutyronitrile and 4.2L dimethyl sulfoxide and add them into a reactor, the temperature of the reactor is raised to 60°C, and after the reaction is kept warm for 2h, 1.0L of modified liquid is added to the reactor, and the reaction is kept warm for 10min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is transferred to a rotary evaporator at a temperature of 80°C, and the solvent is evaporated under reduced pressure to obtain a modified ternary rubber.

[0049] Step 4: Preparation of modified rubber

[0050] Weigh: 210.0 g of modified ternary rubber and 100.0 g of modified polysilicon boron rubber, add them into an internal mixer at a temperature of 200° C., mix for 12 minutes, and discharge the materials to obtain a modified rubber blank;

[0051] Weighing: Place the modified rubber body in an electron beam irradiation device, introduce nitrogen protection into the electron beam irradiation device at a flow rate of 10 L / min, set the electron beam energy to 2 MeV, the power to 18 kW, the radiation dose to 180 kGy, and the conveyor belt speed to 1 m / min to obtain the modified rubber.

[0052] Step 5: Preparation of composite materials

[0053] Weigh: 9.6 kg of modified rubber, 1.2 kg of nano-silica particles, 300.0 g of dibutyl phthalate, 120.0 g of 2,6-di-tert-butylhydroquinone, 200.0 g of epoxidized soybean oil, 200.0 g of polyethylene wax and 500.0 g of thiophenol dicarboxaldehyde, and add them into a twin-screw extruder. The temperatures of the six temperature sections of the twin-screw extruder from the feed end to the discharge end are 200° C., 205° C., 210° C., 210° C., 210° C., 215° C., respectively. The main shaft speed of the twin-screw extruder is 40 rpm. The material is melt-extruded into a molding mold, naturally cooled and shaped to obtain a composite material.

[0054] Example 2

[0055] This embodiment provides a method for preparing a wear-resistant and stretch-resistant composite material for rubber gloves, comprising the following steps:

[0056] Step 1: Preparation of modified particles

[0057] Weigh: 250.0 g of tetraethyl orthosilicate, 450.0 g of zinc nitrate and 2.4 L of deionized water into a reactor, stir at room temperature for 5 min, adjust the pH of the reaction system to 10 with a saturated sodium hydroxide solution, let it stand for 12 h to obtain an aged gel, transfer the aged gel to a drying oven at 80° C. and vacuum dry to constant weight to obtain a mixed gel;

[0058] The mixed gel was transferred to a tubular furnace. After nitrogen protection was introduced into the tubular furnace, the temperature of the tubular furnace was increased to 600° C. at a heating rate of 5° C. / min and kept at this temperature for 4 h to obtain modified particles.

[0059] Step 2: Preparation of modified polysilicon boron rubber

[0060] Weigh: 500.0g modified microparticles, 240.0g 5-chloro-2-methoxyphenylboronic acid, 72.0mL saturated sodium hydroxide solution and 3.2L anhydrous ethanol are added to a three-necked flask in sequence, and the temperature is raised to 60°C under magnetic stirring conditions, the stirring rate is 120rpm, and the constant temperature reaction is maintained for 30min. After the reaction is completed, wait for the temperature of the three-necked flask to drop to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with anhydrous ethanol and deionized water for 5 times, and then place the filter cake in a drying oven at a temperature of 80°C and vacuum dry to constant weight to obtain boronized microparticles;

[0061] Weigh: 900.0g of boronized microparticles, 360.0g of 3-(methacryloyloxy)propyltrimethoxysilane, 420.0g of diphenyldimethoxysilane, 72.0g of triethylamine and 5.4LN,N-dimethylformamide, add them into a three-necked flask in sequence, raise the temperature to 80°C by oil bath heating, and stir and react at this temperature for 2h, then continue to add 150.0g of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane to the system, react for 20min, after the reaction is completed, wait for the temperature of the three-necked flask to drop to room temperature, transfer the reaction solution to a rotary evaporator at a temperature of 90°C, and evaporate the solvent under reduced pressure to obtain modified polysilicon boron rubber.

[0062] Step 3: Modified ternary rubber

[0063] Weigh: 250.0 g of 3-isocyanatepropyltrimethoxysilane, 30.0 g of triethylamine and 1.2 L of dimethyl sulfoxide according to the amount ratio to prepare a modified solution;

[0064] Weigh: 540.0g of allyl methyl disulfide, 360.0g of 2-methacrylamide, 540.0g of 4-allyl-1,2-dimethoxybenzene, 150.0g of azobisisobutyronitrile and 4.2L of dimethyl sulfoxide and add them into a reactor. The temperature of the reactor is raised to 80°C. After the reaction is kept warm for 3 hours, 1.2L of modified liquid is added to the reactor and the reaction is kept warm for 15 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to a rotary evaporator at a temperature of 90°C. The solvent is evaporated under reduced pressure to obtain a modified ternary rubber.

[0065] Step 4: Preparation of modified rubber

[0066] Weigh: 240.0 g of modified ternary rubber and 100.0 g of modified polysilicon boron rubber, add them into an internal mixer at a temperature of 210° C., mix for 15 min, and discharge the materials to obtain a modified rubber blank;

[0067] Weighing: Place the modified rubber body in an electron beam irradiation device, introduce nitrogen protection into the electron beam irradiation device at a flow rate of 15 L / min, set the electron beam energy to 4 MeV, the power to 20 kW, the radiation dose to 240 kGy, and the conveyor belt speed to 3 m / min to obtain the modified rubber.

[0068] Step 5: Preparation of composite materials

[0069] Weigh: 10.0 kg of modified rubber, 1.2 kg of nano-silica particles, 420.0 g of dibutyl phthalate, 160.0 g of 2,6-di-tert-butylhydroquinone, 240.0 g of epoxidized soybean oil, 250.0 g of polyethylene wax and 720.0 g of thiophenol dicarboxaldehyde, and add them into a twin-screw extruder. The temperatures of the six temperature sections of the twin-screw extruder from the feed end to the discharge end are 200° C., 205° C., 210° C., 210° C., 210° C., 215° C., respectively. The main shaft speed of the twin-screw extruder is 60 rpm. The material is melt-extruded into a molding mold, naturally cooled and shaped to obtain a composite material.

[0070] Example 3

[0071] This embodiment provides a method for preparing a wear-resistant and stretch-resistant composite material for rubber gloves, comprising the following steps:

[0072] Step 1: Preparation of modified particles

[0073] Weigh: 270.0 g of tetraethyl orthosilicate, 540.0 g of zinc nitrate and 2.4 L of deionized water into a reactor, stir at room temperature for 10 min, adjust the pH of the reaction system to 10 with a saturated sodium hydroxide solution, let it stand for 12 h to obtain an aged gel, transfer the aged gel to a drying oven at 80° C. and vacuum dry to constant weight to obtain a mixed gel;

[0074] The mixed gel was transferred to a tubular furnace. After nitrogen protection was introduced into the tubular furnace, the temperature of the tubular furnace was increased to 600° C. at a heating rate of 4° C. / min and kept at this temperature for 3 h to obtain modified particles.

[0075] Step 2: Preparation of modified polysilicon boron rubber

[0076] Weigh: 720.0g modified microparticles, 240.0g 5-chloro-2-methoxyphenylboronic acid, 72.0mL saturated sodium hydroxide solution and 3.2L anhydrous ethanol are added to a three-necked flask in sequence, and the temperature is raised to 60°C under magnetic stirring, the stirring rate is 100rpm, and the constant temperature reaction is maintained for 30min. After the reaction is completed, wait for the temperature of the three-necked flask to drop to room temperature, filter the reaction liquid to collect the filter cake, wash the filter cake with anhydrous ethanol and deionized water for 4 times, and then place the filter cake in a drying oven at a temperature of 80°C and vacuum dry to constant weight to obtain boronized microparticles;

[0077] Weigh: 960.0g of boronized microparticles, 480.0g of 3-(methacryloyloxy)propyltrimethoxysilane, 540.0g of diphenyldimethoxysilane, 64.0g of triethylamine and 5.4LN,N-dimethylformamide, add them into a three-necked flask in sequence, raise the temperature to 70°C by oil bath heating, and stir the reaction at this temperature for 2h, then continue to add 160.0g of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane to the system, react for 15min, after the reaction is completed, wait for the temperature of the three-necked flask to drop to room temperature, transfer the reaction solution to a rotary evaporator at a temperature of 90°C, and evaporate the solvent under reduced pressure to obtain modified polysilicon boron rubber.

[0078] Step 3: Modified ternary rubber

[0079] Weigh: 240.0 g of 3-isocyanatepropyltrimethoxysilane, 24.0 g of triethylamine and 1.0 L of dimethyl sulfoxide according to the amount ratio to prepare a modified solution;

[0080] Weigh: 540.0g of allyl methyl disulfide, 360.0g of 2-methacrylamide, 540.0g of 4-allyl-1,2-dimethoxybenzene, 150.0g of azobisisobutyronitrile and 4.2L of dimethyl sulfoxide and add them into a reactor. The temperature of the reactor is raised to 70°C. After the reaction is kept warm for 3 hours, 1.2L of modified liquid is added to the reactor and the reaction is kept warm for 12 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to a rotary evaporator at a temperature of 90°C. The solvent is evaporated under reduced pressure to obtain a modified ternary rubber.

[0081] Step 4: Preparation of modified rubber

[0082] Weigh: 250.0 g of modified ternary rubber and 100.0 g of modified polysilicon boron rubber, add them into an internal mixer at a temperature of 210° C., mix for 15 min, and discharge the materials to obtain a modified rubber blank;

[0083] Weighing: Place the modified rubber body in an electron beam irradiation device, introduce nitrogen protection into the electron beam irradiation device at a flow rate of 12 L / min, set the electron beam energy to 3 MeV, the power to 18 kW, the radiation dose to 210 kGy, and the conveyor belt speed to 2 m / min to obtain the modified rubber.

[0084] Step 5: Preparation of composite materials

[0085] Weigh: 9.6 kg of modified rubber, 1.5 kg of nano-silica particles, 420.0 g of dibutyl phthalate, 160.0 g of 2,6-di-tert-butylhydroquinone, 210.0 g of epoxidized soybean oil, 240.0 g of polyethylene wax and 720.0 g of thiophenol dicarboxaldehyde and add them into a twin-screw extruder, the temperatures of the six temperature sections of the twin-screw extruder from the feed end to the discharge end are 200° C., 205° C., 210° C., 210° C., 210° C., 215° C., the main shaft speed of the twin-screw extruder is 50 rpm, melt extruded into a molding mold, naturally cooled and shaped to obtain a composite material.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 3 is that in step 1, an equal amount of ethyl orthosilicate is used to replace zinc nitrate.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 3 is that in step 2, 3-(methacryloyloxy)propyltrimethoxysilane is used to replace 5-chloro-2-methoxyphenylboronic acid in an equal amount.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 3 is that in step 3, an equal amount of acrylic acid ester is used to replace allyl methyl disulfide.

[0092] Performance Test:

[0093] The volume wear of the composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)";

[0094] The tensile strength and elongation at break of the composite materials prepared in Examples 7-9 and Comparative Examples 1-3 were tested with reference to the standard GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber";

[0095] The vertical combustion grades of the composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were determined with reference to the standard GB / T 2408-2021 “Horizontal and vertical methods for determination of combustion performance of plastics”;

[0096] The limiting oxygen index of the composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test". The specific data are shown in Table 1.

[0097] Table 1-Performance data of each sample

[0098]

[0099]

[0100] Data Analysis:

[0101] Comparing and analyzing the data in Table 1 above, the volume wear of the composite material prepared by the present invention is 25.6 mm 3 , tensile strength is 37.2MPa, elongation at break is 751.2%, vertical burning grade is V-0 and limiting oxygen index is 38.3%, all data are better than the comparative example;

[0102] By comparing the data of Example 3 and Comparative Example 1, it can be found that the volume wear of the composite material prepared in Comparative Example 1 is significantly increased, and the tensile strength and elongation at break are significantly reduced, indicating that after zinc nitrate is added in the process of preparing the modified microparticles, the zinc nitrate is hydrolyzed and calcined to produce an oxidizing component, which, as a component of the modified microparticles, is polymerized with the silicon-based monomer after boronization to form a modified polysilicon boron rubber. The internal zinc oxide component activates the disulfide bonds inside the modified ternary rubber during the process of melt extrusion with the modified ternary rubber, promotes the disulfide bonds to be exercised to form a cross-linked structure, and generates a large amount of heat as a radiation absorption center during the electron radiation process, promotes the large number of double bonds on the modified polysilicon boron rubber and the internal chain segments of the modified ternary rubber to break to produce free radicals, and further hybridizes the organic chain segments, thereby significantly improving the wear resistance and tensile resistance of the material;

[0103] By comparing the data of Example 3 and Comparative Example 2, it can be found that the flame retardant performance of the composite material prepared in Comparative Example 2 is significantly reduced, indicating that the boronized particles obtained after the surface of the modified particles is boronized as the polymerization center of the modified polysilicon boron rubber. During the combustion of the material, the boron-oxygen chain segments will generate a glassy protective layer covering the surface of the material, isolating oxygen, reducing the contact between the combustible and the heat source, thereby inhibiting the continuation of the combustion reaction. In addition, the glassy protective layer has a high heat capacity and can absorb part of the heat during combustion, reduce the surface temperature of the material, delay the combustion process, and burn with the silicon-oxygen chain segments to produce silicon dioxide, further forming an inorganic glassy protective film to prevent the combustion from spreading. In addition, the boron element can also catalyze the formation of a carbonized layer on the surface of the material, thereby achieving heat insulation and oxygen isolation effects, further inhibiting the spread of flames.

[0104] In addition, the mechanical properties of the material also decrease to a certain extent, indicating that the introduction of boron elements enables the modified polysilicon boron rubber to form a cross-linked network composed of boron oxygen bonds and silicon oxygen bonds. Boron oxygen bonds can provide additional chemical cross-linking points, greatly increasing the cross-linking density of the material, thereby reducing the slippage and breakage of the molecular chain, allowing the material to withstand higher stress when subjected to force, and the cross-linking structure is tighter, and the tensile strength and elongation of the material are also improved; and compared with silicon oxygen bonds, boron oxygen bonds have higher rigidity and stronger tensile properties, and enhance the interaction between molecular chains, so that the material is not easy to deform under the action of external force, and can absorb and disperse more mechanical energy when subjected to force;

[0105] By comparing the data of Example 3 and Comparative Example 3, it can be found that the volume wear of the composite material prepared in Comparative Example 3 is significantly increased, and the tensile strength and elongation at break are significantly reduced, indicating that the introduction of disulfide bonds inside the rubber can dynamically adjust the structure of the cross-linked network when the crack propagates, thereby delaying the propagation of the crack, thereby improving the tensile resistance and elongation at break of the material; and, compared with the traditional single sulfur bond, the chain segment of the disulfide bond is longer, so that the cross-linked network has greater freedom and flexibility, thereby improving the ductility of the rubber, thereby generating a flexible cross-linked network, and the flexible cross-linked network reduces the risk of fracture under cyclic stress, thereby improving the elongation at break of the material. This network also significantly enhances the wear resistance of the material. At the same time, when the EPDM rubber is melt-blended with the modified polysilicon boron rubber, the zinc oxide component inside the modified polysilicon boron rubber promotes the rupture of the disulfide bonds to form active free radicals, thereby realizing cross-linking inside the chain segment, thereby significantly improving the mechanical properties of the material;

[0106] The present invention prepares expanded particles, which serve as polymerization bases of modified polysilicon boron rubber, promote the breaking of disulfide bonds inside the modified ternary rubber to form active sites, promote the vulcanization and crosslinking of the modified ternary rubber and the modified polysilicon boron rubber, and at the same time, serve as radiation absorption centers to further promote the crosslinking of the two, thereby significantly improving the mechanical properties of the material. In addition, its silicon-boron structure generates a glassy protective layer covering the surface of the material during combustion, and its boron-oxygen structure promotes carbonization of organic matter, so that the material forms a heat-insulating carbon layer, thereby significantly improving the flame retardant properties of the material.

[0107] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0108] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0109] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A wear-resistant and tensile-resistant composite material for rubber gloves, characterized in that: The raw material composition includes the following parts by weight: 80-100 parts of modified rubber, 10-15 parts of filler, 3-5 parts of plasticizer, 1-2 parts of antioxidant, 2-3 parts of heat stabilizer, 2-3 parts of lubricant and 5-8 parts of vulcanizer; The preparation method of the modified rubber comprises the following steps: A1. Add the modified ternary rubber and modified polysilicon boron rubber into an internal mixer at a temperature of 200-210°C, mix for 12-15 minutes, and discharge the materials to obtain a modified rubber body; A2. Placing the modified rubber body in an electron beam irradiation device to obtain the modified rubber after electron irradiation.

2. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 1, characterized in that: In step A1, the usage ratio of modified ternary rubber and modified polysilicon boron rubber is 2-3g:1g; in step A2, the operation of electron irradiation is: nitrogen protection is introduced into the electron beam irradiation equipment at a flow rate of 10-15L / min, and the electron beam energy is set to 2-4MeV, the power is 18-20kW, the radiation dose is 180-240kGy, and the conveyor belt speed is set to 1-3m / min.

3. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 1, characterized in that: The preparation method of the modified ternary rubber is as follows: allyl methyl disulfide, 2-methyl acrylamide, 4-allyl-1,2-dimethoxybenzene, azobisisobutyronitrile and dimethyl sulfoxide are added to a reaction kettle, the temperature of the reaction kettle is increased to 60-80°C, and the reaction is carried out by heat preservation for 2-3 hours, and then a modification liquid is added to the reaction kettle, and the reaction is carried out by heat preservation for 10-15 minutes, and the modified ternary rubber is obtained by post-treatment.

4. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 3, characterized in that: The dosage ratio of allyl methyl disulfide, 2-methylacrylamide, 4-allyl-1,2-dimethoxybenzene, azobisisobutyronitrile, dimethyl sulfoxide and modification liquid is 5-6g:3-4g:5-6g:1.2-1.6g:40-50mL:10-12mL, and the modification liquid is composed of 3-isocyanatepropyltrimethoxysilane, triethylamine and dimethyl sulfoxide in a dosage ratio of 2-3g:0.2-0.3g:10-12mL.

5. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 1, characterized in that: The preparation method of the modified polysilicon boron rubber comprises the following steps: B1. Add the modified microparticles, 5-chloro-2-methoxyphenylboronic acid, saturated sodium hydroxide solution and anhydrous ethanol to a three-necked flask in sequence, heat to 50-60° C. under magnetic stirring, and keep the constant temperature for 20-30 minutes. After the reaction is completed, perform post-treatment to obtain boronized microparticles; B2. Add boronated particles, 3-(methacryloyloxy)propyltrimethoxysilane, diphenyldimethoxysilane, triethylamine and N,N-dimethylformamide into a three-necked flask in sequence, raise the temperature to 60-80°C by oil bath heating, and stir the reaction at this temperature for 1-2 hours, then continue to add the end-capping agent to the system and react for 10-20 minutes. After the reaction is completed, perform post-treatment steps to obtain modified polysilicon boron rubber.

6. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 5, characterized in that: In step B1, the magnetic stirring rate is 80-120rpm, and the amount ratio of modified zinc oxide particles, 5-chloro-2-methoxyphenylboric acid, saturated sodium hydroxide solution and anhydrous ethanol is 5-8g:2-3g:0.5-0.8mL:30-40mL; in step B2, the amount ratio of boronated particles, 3-(methacryloyloxy)propyltrimethoxysilane, diphenyldimethoxysilane, triethylamine, N,N-dimethylformamide and end-capping group is 8-10g:3-5g:4-6g:0.5-0.8g:50-60mL:1-2g, and the end-capping agent is 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane.

7. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 5, characterized in that: The preparation method of the modified microparticles comprises the following steps: C1. Add tetraethyl orthosilicate, zinc nitrate and deionized water into a reaction kettle, stir at room temperature for 5-10 minutes, adjust the pH of the reaction system to 8-10 with a saturated sodium hydroxide solution, let stand for 8-12 hours to obtain an aged gel, and perform post-treatment to obtain a mixed gel; C2. Transfer the mixed gel to a tubular furnace and calcine to obtain modified particles.

8. The wear-resistant and tensile-resistant composite material for rubber gloves according to claim 7, characterized in that: In step C1, the dosage ratio of ethyl orthosilicate, zinc nitrate and deionized water is 2-3g:4-6g:20-30mL; in step C2, the calcination operation includes: after nitrogen protection is introduced, the tubular furnace is heated to 500-600°C at a heating rate of 3-5°C / min, and the temperature is kept for 2-4h to obtain modified particles.

9. The method for preparing the wear-resistant and tensile-resistant composite material for rubber gloves according to claims 1-8, characterized in that: The method comprises the following steps: adding modified rubber, modified particles, plasticizer, antioxidant, heat stabilizer, lubricant and vulcanizer into a twin-screw extruder, melting and extruding into a forming mold, and naturally cooling and shaping to obtain a composite material.

Citation Information

Patent Citations

  • Wear-resisting rubber gloves and processing method thereof

    CN103549689A